Properties and Design of Double Skin Facade in the Tropics - Khairdzir, Norhazwani; Taib, Nooriati (MAJ - Malaysia Architectural Journal, 2020)
On average, a person spends more than 70% of their life inside buildings Thus, a comfortable indoor environment has a vital role as not only can it improves the people’s working efficiency, but also sustain their health. The building envelope or skin is the most critical aspect to be considered in designing a comfortable indoor environment for occupation. Theoretically, the application of Double Skin Façade (DSF) system is said to be an attempt towards sustainable design as it creates a controlled ventilated buffer area between the outside environment and the indoor climate of the building. However, several research shows that it might be the opposite for DSF applied in the tropics, especially since previous studies are mostly done in temperate climate countries. This research aims to study the properties and identify design consideration of DSF application in hot and humid climate. Three case study buildings in Malaysia with Double Skin Facade (DSF) are selected and analyse through comparative study based on similarity of characteristics, difference approach and design considerations. In this paper, it will also be discussed how the design considerations of DSF might affect the Indoor Environment Quality (IEQ). Design considerations for building envelope is needed to increase the awareness towards quality of indoor environment and its influence on occupant’s comfort.